Military Art of The Peoples of Central Asia Against the Troops of Genghis Khan in The Middle Ages - Sarvar Turaev (Zien Journals, 2024)
The article talks about the peoples of Central Asia in the Middle Ages against the aggressive actions of the troops of Genghis Khan/ o the tactics used by the two sides, tactical techniques, form, methods of combat by the Khorezmshah and Mongols.
Keywords: tactical techniques,; harassment; mamluk; warrior